Characterization of monoclonal antibodies raised against p300: both p300 and CBP are present in intracellular TBP complexes. - Dallas, P B (1997)
The amino terminus of the adenovirus E1A protein is involved in E1A transforming functions, repression of tissue-specific gene expression, and E1A-mediated enhancer repression. These N-terminal functions are associated with the ability of this region of E1A to bind to p300 and CBP, two closely related cellular proteins thought to function as transcriptional adaptor molecules. Here we describe the characterization of a panel of 11 monoclonal antibodies raised against E1A-affinity-purified 300-kDa proteins. The panel can be divided into two groups based on immunoprecipitation patterns. The first group consists of five p300/CBP-cross-reactive and two p300-specific monoclonal antibodies, all of which immunoprecipitate p300 and/or CBP without associated cellular proteins. In contrast, the second group immunoprecipitates p300 or both p300 and CBP in association with a complex of at least seven other cellular proteins. Taking advantage of the specificities of these monoclonal antibodies, we have identified both p300 and CBP in in vivo complexes with TBP, a finding consistent with a role for both p300 and CBP in promoting interactions between upstream promoter elements and the basal transcription apparatus.